Gender in Amazonia and Melanesia : an exploration of the comparative method - Gregor, Thomas; Tuzin, Donald F. (University of California Press, 2001)
One of the great riddles of cultural history is the remarkable parallel that exists between the peoples of Amazonia and Melanesia. Although the two regions are separated by half a world in distance and at least 40,000 years of history, their cultures nonetheless reveal striking similarities in the areas of sex and gender. The contributors illuminate the various ways in which sex and gender are elaborated, obsessed over, and internalized, shaping subjective experiences common to entire cultural regions, and beyond.